Réponses

  • carys
  • Modératrice confirmée
2013-03-11T18:42:48+01:00

a+b(c+d) = a + bc + bd

a (b+c)(d+e) = (ab + ac)(d+e)

                       = abd + abe + acd + ace

( a+b)(c+d)(e+f) = (ac + ad + bc + bd)(e + f)
                             = ace + acf + ade + adf + bce + bcf + bde + bdf


( a+b)(c+d)-(e+f)(g+h)= ac + ad + bc + bd - eg - eh - fg - fh

( a+b)(c+d)+(e+f)(g+h)= ac + ad + bc + bd + eg + eh + fg + fh

 

voilà :)

2013-03-11T18:43:12+01:00
A x c + a x d + b x c + b x d

a x b + a x c + a x d + a x e

a x c + a x d + b x c + b x d - ( e x g + e x h + f x g + f x h ).
Pour la dernière c'est pareil sauf qu'à la place du - c'est un + .